Perancangan Visual Emote Digital Magenta Gurl dalam menyampaikan Ekspresi Emosi pada Platform Live Streaming - Nazlyna Salsa Billa; Wandah Wibawanto (Lembaga Pengembangan Kinerja Dosen, 2026)
. The development of live streaming culture has encouraged the use of digital emotes as a visual communication medium and a means of expression between streamers and viewers. This study aims to design digital emotes based on the original character Magenta Gurl as a medium of expression for live streaming platforms. The study was motivated by the limited research on the visual design of digital emotes, despite their potential to serve as personalized communication media through illustrations that can be customized to reflect users' visual identities. The research employed a design approach using literature review, observation, and visual documentation as data collection methods. The design process included design requirements analysis, character concept development, emotional expression selection, sketch creation, illustration digitization, and emote implementation on the BetterTTV platform. The design resulted in six digital emotes featuring various expressions that support interaction during live streaming. All emotes were successfully implemented on BetterTTV by complying with the platform's required format and technical specifications, enabling them to function as visual communication media that facilitate interaction and deliver emotional expression in a more personalized manner within live streaming platforms.